Penerapan Pola Asuh Gizi untuk Menunjang Penanggulangan Stunting pada Balita - Safyanti; Hasneli; Andrafikar; Gusnedi; Neni Fitra Hayati (CV. CENDIKIA JENIUS INDONESIA, 2025)
The working area of the Sirukam Public Health Center, Payung Sekaki Subdistrict, Solok Regency, is a region with the highest prevalence of stunting in the area. This issue is closely related to the low quality of nutritional parenting practices among housewives, particularly in the utilization and processing of local food ingredients. This community service activity aims to implement nutritional parenting practices to support stunting prevention in toddlers. The methods used include education, discussions, and hands-on practice in preparing nutritious meals for toddlers using local food ingredients. The intervention was carried out in three villages using a training and household mentoring approach. Evaluation was conducted through pre-tests and post-tests to measure the improvement in knowledge and skills of mothers with toddlers. The results showed a significant increase in mothers' knowledge regarding the provision of balanced nutritious food for toddlers, from 42.9% (good) before the intervention to 76.3% afterward. In conclusion, intensive and continuous mentoring proved effective in improving mothers' abilities in nutritional parenting for toddlers and holds great potential in supporting efforts to accelerate stunting reduction in the area.